A critical review of fabrication challenges and reliability issues in top/bottom gated MoS2 field-effect transistors. (4th June 2023) - Thoutam, Laxman Raju; Mathew, Ribu; Ajayan, J; Tayal, Shubham; Nair, Shantikumar V
Abstract: The voyage of semiconductor industry to decrease the size of transistors to achieve superior device performance seems to near its physical dimensional limitations. The quest is on to explore emerging material systems that offer dimensional scaling to match the silicon- based technologies. The discovery of atomic flat two-dimensional materials has opened up a completely new avenue to fabricate transistors at sub-10 nanometer level which has the potential to compete with modern silicon-based semiconductor devices. Molybdenum disulfide (MoS2 ) is a two-dimensional layered material with novel semiconducting properties at atomic level seems like a promising candidate that can possibly meet the expectation of Moore's law. This review discusses the various ' fabrication challenges ' in making MoS2 based electronic devices from start to finish. The review outlines the intricate challenges of substrate selection and various synthesis methods of mono layer and few-layer MoS2 . The review focuses on the various techniques and methods to minimize interface defect density at substrate/MoS2 interface for optimum MoS2 -based device performance. The tunable band-gap of MoS2 with varying thickness presents a unique opportunity for contact engineering to mitigate the contact resistance issue using different elemental metals. In this work, we present a comprehensive overview of different types of contact materials with myriad geometries that show a profound impact on device performance. The choice of different insulating/dielectric gate oxides on MoS2 in co-planar and vertical geometry is critically reviewed and the physical feasibility of the same is discussed. The experimental constraints of different encapsulation techniques on MoS2 and its effect on structural and electronic properties are extensively discussed.